Ottoman Foundations in Chios - Taş, Mehmet (Eximia, 2024)
Chios Island is one of the important islands located in the Sea of Islands. It remained under Ottoman rule for approximately 347 years from 1566 to 1913. While the Ottomans established their own administration here after the conquest, they also brought the traditional Turkish-Islamic culture to the island. The elements of this culture, such as love for humanity, respect for differences, peace, tolerance and sacrifice, were brought to the island through foundations. While the foundations ensured the continuation of the Turkish presence here with the mosques, mescits, dervish lodges and zawiyas they established, they played a certain role in the economic and commercial life of the island with structures such as inns, shops, bazaars, plots of land and mills. Foundations were established by both members of the Ottoman dynasty and statesmen. Knowing these will make it possible to make a more accurate assessment of the Ottoman administration on the island. The Ottomans created many architectural and cultural works on this island. Among these are many mosques, masjids, fountains, public fountains, baths, lodges and zawiyas. Some of these are the Hamidiye Mosque, Bayraktar Mosque, Piyale Pasha Mosque, Misirlizade Ibrahim Pasha Mosque and Foundation, Salih Pasha Mosque and Madrasah, Melek Mehmet Pasha Fountain and Laleli Mosque. According to state records from 1894, there were nine mosques, two madrasahs, three lodges, ninety-eight churches, one monastery, two synagogues, two baths and eighteen fountains on the island. Today, there are eight mosques, one masjid, one lodge, three baths, one fountain and one inn in Chios as Ottoman works. Some of these will be discussed in this study.